Disaster playground [videorecording (DVD)] - Boslough, Mark; Boyd, John W.; Chesley, Steven (Kino Lorber, 2016)
Viewers will follow the scientists planning and monitoring the deflection of hazardous near Earth objects and the real-life procedures in place in the event of an asteroid collision with the earth. From the SETI Institute and NASA to the White House and United Nations, viewers will meet the people who are responsible for protecting the planet from a potentially devastating asteroid impact.